2009
DOI: 10.1073/pnas.0907078106
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral tagging is a general mechanism of long-term memory formation

Abstract: In daily life, memories are intertwined events. Little is known about the mechanisms involved in their interactions. Using two hippocampus-dependent (spatial object recognition and contextual fear conditioning) and one hippocampus-independent (conditioned taste aversion) learning tasks, we show that in rats subjected to weak training protocols that induce solely short term memory (STM), long term memory (LTM) is promoted and formed only if training sessions took place in contingence with a novel, but not famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
311
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(348 citation statements)
references
References 36 publications
31
311
5
1
Order By: Relevance
“…Recently, several studies have shown that memories can interact with each other by means of synaptic tagging and capture (Almaguer-Melian et al, 2012;Ballarini et al, 2009;Moncada and Viola, 2007;Wang et al, 2010;Myskiw et al, 2013). All these studies show that exposure to novelty can upregulate the synthesis of PRPs, presumably through the release of dopamine, which are then captured at tagged synapses in a cooperative fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have shown that memories can interact with each other by means of synaptic tagging and capture (Almaguer-Melian et al, 2012;Ballarini et al, 2009;Moncada and Viola, 2007;Wang et al, 2010;Myskiw et al, 2013). All these studies show that exposure to novelty can upregulate the synthesis of PRPs, presumably through the release of dopamine, which are then captured at tagged synapses in a cooperative fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the memory-stabilizing effect of dopamine extends to other information encoded when dopamine is available, a phenomenon also referred to as the 'penumbra hypothesis' (Lisman et al, 2011). The hypothesis predicts that once dopamine availability is enhanced, any encoded information will benefit from preferential consolidation, regardless of the actual trigger of the dopamine release (Lisman et al, 2011), and initial evidence from rodent (Ballarini et al, 2009; and human (Fenker et al, 2008;Wittmann et al, 2011) data points out that it may indeed be so. Boosts in dopamine availability at encoding thus result in memory being more stable and better protected from forgetting, an effect that may predominantly arise at long (>24 h) but not short time intervals after learning, highlighting the role of memory consolidation processes and sleep in dopaminergic modulation of memory traces (See Box 2 on the role of sleep in consolidation; Perogamvros and Schwartz, 2012).…”
Section: Role Of Dopamine In Learning and Memory Consolidationmentioning
confidence: 99%
“…For this, we studied the role of hippocampal protein synthesis on the extinction facilitation by novelty through bilateral infusion into the CA1 region of the hippocampus of the protein synthesis inhibitor anisomycin (ANI) (12,13) after exposing the animals to the novelty. In addition, we examined the influence of hippocampal dopamine on this effect, in particular whether it is mediated by D1 or D5 receptors.…”
Section: Significancementioning
confidence: 99%
“…This influence is explainable by interactions between new proteins, called plasticity-related proteins (PRPs), at the two sets of synapses; the PRPs that tag one of them can be captured by those of others and enhance their responsiveness (3)(4)(5). Many memories rely on hippocampal LTP and LTD (1,2,(6)(7)(8)(9)(10)(11), and the "synaptic tagging-and-capture" process has been applied to the explanation of interactions between concurrent memories (11)(12)(13), among which are novelty and fear acquisition (12,14) and novelty and fear extinction (15,16). Exposure to novelty [an open field (OF) in which they had never been before] involves two consecutive processes: its detection, which is very brief (seconds), and the immediately ensuing habituation (17), which lasts much longer; both rely on hippocampal LTD (18).…”
mentioning
confidence: 99%